Sakis Gekas, Xenocracy: State, Class and Colonialism in the Ionian Islands, 1815–1864 - Zanou, Konstantina (Historein, 2018)
Review of Sakis Gekas, Xenocracy: State, Class and Colonialism in the Ionian Islands, 1815–1864. New York/Oxford: Berghahn, 2017. 380 pp.